2015
DOI: 10.1245/s10434-015-4595-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-184 Deregulated by the MicroRNA-21 Promotes Tumor Malignancy and Poor Outcomes in Non-small Cell Lung Cancer via Targeting CDC25A and c-Myc

Abstract: MiR-184 as a tumor suppressor miR inhibits cell proliferation and invasion capability via targeting CDC25A and c-Myc. Low miR-184 level may predict worse prognosis in NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…41 As suggested by various studies, miR-184 might be a useful diagnostic and therapeutic tool for malignant diseases. 38,39 However, to the best of our knowledge, ours is the first study to provide data about miR-184 expression in EC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…41 As suggested by various studies, miR-184 might be a useful diagnostic and therapeutic tool for malignant diseases. 38,39 However, to the best of our knowledge, ours is the first study to provide data about miR-184 expression in EC.…”
Section: Discussionmentioning
confidence: 92%
“…In the same way, miR-184 functions as a tumor suppressor in various cancers (renal carcinoma, 36 glioma, 37,38 non-small-cell lung cancer, 39 oral squamous cell carcinoma, 40 breast cancer 41 ) by repressing oncogenes such as TNFAIP2, 37 SND1, 38 CDC25A, c-MYC, 39 and regulating the AKT/mTORC1 pathway. 41 As suggested by various studies, miR-184 might be a useful diagnostic and therapeutic tool for malignant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a low expression level of miR-184 may be a predictor of poor prognosis in patients with non-small cell lung cancer. Upregulation of miR-184 decreased cell proliferation and invasion by targeting cell division cycle 25A and c-Myc (31). In renal cell carcinoma, overexpression of miR-184 suppressed cell proliferation and migration, and enhanced cell apoptosis in vitro (28).…”
Section: Discussionmentioning
confidence: 98%
“…It has been identified to be upregulated in hepatocellular carcinoma (26) and squamous cell carcinoma of the tongue (27). However, downregulation of miR-184 has also been identified in various types of human cancer, including renal cell carcinoma (28), nasopharyngeal carcinoma (29), neuroblastoma (30), non-small cell lung cancer (31), glioma (32,33) and breast cancer (32). The contradictory results of these studies indicated that the expression levels of miR-184 in cancer exhibit tissue-specificity.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-184 directly targets c-Myc to suppress cell growth in non-small cell lung cancer (NSCLC) [4]. We recently reported that a decrease in miR-184 by miR-21 promotes tumor malignancy and poor outcomes in non-small cell lung cancer (NSCLC) via targeting CDC25A and c-Myc [5]. Therefore, miR-184 might play a tumor suppressor role in NSCLC.…”
Section: Introductionmentioning
confidence: 99%